Contributions of Various Radiological Sources to Background in a Suburban Environment. Issue 3 (November 2016) - Milvenan, Richard D.; Hayes, Robert B.
Abstract : Abstract: This work is a brief overview and comparison of dose rates stemming from both indoor and outdoor natural background radiation and household objects within a suburban environment in North Carolina. Combined gamma and beta dose rates were taken from indoor objects that ranged from the potassium in fruit to the americium in smoke detectors. For outdoor measurements, various height and time data samples were collected to show fluctuations in dose rate due to temperature inversion and geometric attenuation. Although each sample tested proved to have a statistically significant increase over background using Students t-test, no sample proved to be more than a minor increase in natural radiation dose. The relative contributions from natural radioactivity such as potassium in foods and common household items are shown to be easily distinguished from background using standard handheld instrumentation when applied in a systematic, methodological manner.